2022
DOI: 10.1093/hmg/ddac168
|View full text |Cite
|
Sign up to set email alerts
|

An enhancer variant associated with breast cancer susceptibility in Black women regulates TNFSF10 expression and antitumor immunity in triple-negative breast cancer

Abstract: Women of African ancestry have the highest mortality from triple-negative breast cancer (TNBC) of all racial groups. To understand the genomic basis of breast cancer in the populations, we previously conducted genome-wide association studies (GWAS) and identified single nucleotide polymorphisms (SNPs) associated with breast cancer in Black women. In this study, we investigated the functional significance of the top associated SNP rs13074711. We found the SNP served as an enhancer variant and regulated TNFSF10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Notably, immune-related genes such as TNFSF10, NEDD4, HSPA2, MMP12, CDKN1A, and NGFR exhibited reduced expression, while FABP5, ISG20L2, OGFR, AEN, CCN2, and GSEC showed increased expression. For instance, TNFSF10-deficiency in breast tumors has been linked to decreased tumor-infiltrating CD4+ and CD8+ T cells in a mouse model of breast cancer [ 45 ]. High NEDD4 expression in melanoma tissue is associated with poor patient prognosis and promotes tumor progression by inhibiting T-cell-mediated killing of melanoma cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, immune-related genes such as TNFSF10, NEDD4, HSPA2, MMP12, CDKN1A, and NGFR exhibited reduced expression, while FABP5, ISG20L2, OGFR, AEN, CCN2, and GSEC showed increased expression. For instance, TNFSF10-deficiency in breast tumors has been linked to decreased tumor-infiltrating CD4+ and CD8+ T cells in a mouse model of breast cancer [ 45 ]. High NEDD4 expression in melanoma tissue is associated with poor patient prognosis and promotes tumor progression by inhibiting T-cell-mediated killing of melanoma cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported an association between TNFSF10 and the progression of osteosarcoma (Kamihara et al 2020 ). The findings of Yoo Jane Han suggest that TNFSF10 plays an important role in regulating the antiviral immune response in triple-negative breast cancer (TNBC) (Han et al 2022 ). One study identified ETS2 inhibition as a potential therapeutic target for p53 mutant osteosarcoma (Pourebrahim et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study deleted the TNFSF10 gene from TNBC cells using CRISPR-Cas9 technology and stimulated cells with either poly (I:C), a synthetic analogue of double-stranded RNA virus, or IFN-β, and found that depletion of TNFSF10 clearly reduced poly (I:C)-induced or IFN-β-induced apoptosis 39 . Furthermore, the researcher edited rs13074711, the risk variant reported in previous GWAS 38 , using CRISPR-Cas9 technology, and found it altered TNFSF10 expression and IFN-β-induced apoptosis 39 . Taken together, there is strong evidence that TNFSF10 is a possible cancer suppressor responsible for GWAS signal in 3q26.21 through immune defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%